Effects of inhaled beclomethasone dipropionate/formoterol fumarate/glycopyrronium on diaphragmatic workload and lung function in uncontrolled asthma: a case report - Maiorano, Antonio; Lupia, Chiara; Montenegro, Nicola; Neri, Giuseppe; Bruni, Andrea; Garofalo, Eugenio; Longhini, Federico; Crimi, Claudia; Maglio, Angelantonio; Vatrella, Alessandro; Pelaia, Girolamo; Pelaia, Corrado (Frontiers in Medicine, 2024)
Beclomethasone dipropionate/formoterol fumarate/glycopyrronium (BDP/FF/G) single inhaler extrafine triple therapy is effective for the treatment of uncontrolled asthma. Nevertheless, there is a lack of data about the use of diaphragmatic ultrasonography to monitor adult asthmatics while they are receiving inhaled treatment. We took into consideration a 78-year-old woman complaining of asthma, treated with inhaled corticosteroid/long-acting β2-adrenergic agonist (ICS/LABA), characterized by an asthma control questionnaire-5 (ACQ-5) score and a lung function test suggestive of uncontrolled asthma. Moreover, a diaphragmatic ultrasound showed signs of high diaphragm workload. Because of these findings, we proposed to our patient a shift toward triple inhaled therapy with BDP/FF/G, and she underwent a second evaluation after 7 days of treatment. Improvements in the diaphragmatic ultrasound parameters, lung function test, and ACQ-5 score were found. In particular, we detected a reduction of thickening fraction (TF), and a normalization of the other diaphragmatic measures, indicative of a decrease in diaphragmatic workload. To our knowledge, this is the first literature report showing concomitant improvements of both lung function tests and diaphragmatic ultrasonography parameters, observed in an adult patient with uncontrolled asthma after short-term treatment with the single inhaler triple therapy BDP/FF/G.